Internalisasi Nilai-Nilai Pendidikan Agama Hindu Melalui Wisata Spiritual Berbasis Heritage di Bebaturan Pura Pulung Sari Buleleng - Pradna Lagatama (Jayapangus Press, 2026)
The development of spiritual tourism in Bali faces serious challenges in the form of desacralization due to the commodification of rituals and the reduction of spiritual meaning to mere visual attractions. This situation demands strengthening the educational dimension of living heritage sites that still function religiously. This study aims to analyze the process of internalizing Hindu religious education values ​​through heritage-based spiritual tourism at the Pulung Sari Temple Boundary in Buleleng Regency. The study used a descriptive qualitative approach with a pedagogical phenomenology perspective. Data were collected through participant observation, in-depth interviews, and documentation studies of ritual practices, spatial structures, and the spiritual experiences of worshippers and tourists. The results indicate that internalization of values ​​occurs through a mechanism formulated as the pedagogy of megalithic silence. This concept refers to a spiritual learning model based on ritual silence, material simplicity, and direct interaction with megalithic stone structures as media for transcendental reflection. This study differs from previous spiritual tourism research by positioning heritage-based sacred sites not as tourism attractions or economic assets, but as non-formal Hindu religious education spaces where educational values are internalized experientially. Within this mechanism, the values ​​of Tattwa are internalized through an inclusive theology that unites megalithic traditions and Vedic teachings. The values ​​of Susila are embedded through an ethic of simplicity and adherence to the bhisama (silence without bells) that reduces ego and materialism. While the values ​​of Ceremony are manifested through the practice of Tirthayatra, a form of experiential learning that emphasizes spiritual independence and personal endeavor. The novelty of this research lies in the conceptual formulation of the pedagogy of megalithic silence as a model of non-formal Hindu religious education based on sacred sites, which transcends previous approaches to spiritual tourism that were predominantly oriented toward tourism experiences or economic value. This study concludes that the integration of educational values ​​into spiritual tourism can transform Pulung Sari Temple into a laboratory for non-formal education, while simultaneously shifting the relationship between tourists from the tourist gaze to spiritual participation, which supports the preservation of the temple's sanctity and cultural sustainability.